(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The modernization of higher pedagogical education and the increasing requirements for the professional competence of teachers necessitate the improvement of future teachers’ professional and communicative culture. Professional and communicative culture is considered an integrative personal quality that combines communicative competence, professional ethics, speech culture, pedagogical responsibility, and reflective abilities. In this regard, the deontological approach serves as an effective methodological basis for the development of future teachers’ professional and communicative culture. The purpose of this study is to substantiate theoretically a model for developing the professional and communicative culture of future teachers based on a deontological approach and to determine its structural components. The study employed theoretical methods such as analysis, synthesis, comparison, systematization, and pedagogical modeling. As a result, a structural functional model was developed, including target, methodological, content, technological, and diagnostic blocks.